2014
DOI: 10.1104/pp.113.224683
|View full text |Cite
|
Sign up to set email alerts
|

The Coordination of C4 Photosynthesis and the CO2-Concentrating Mechanism in Maize and Miscanthus × giganteus in Response to Transient Changes in Light Quality    

Abstract: Unequal absorption of photons between photosystems I and II, and between bundle-sheath and mesophyll cells, are likely to affect the efficiency of the CO 2 -concentrating mechanism in C 4 plants. Under steady-state conditions, it is expected that the biochemical distribution of energy (ATP and NADPH) and photosynthetic metabolite concentrations will adjust to maintain the efficiency of C 4 photosynthesis through the coordination of the C 3 (Calvin-Benson-Bassham) and C 4 (CO 2 pump) cycles. However, under tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
(89 reference statements)
2
15
0
Order By: Relevance
“…In fact, using the full formulation of the Δ 13 Cleaf model developed byFarquhar (1984) typically indicates little to no change in φ under low light[17,36,37,41]. Additionally, φ was generally found to acclimate to rapid changes in light quality[42]. Therefore, direct measurements of Δ 13 Cleaf generally indicate that C4 plants have a remarkable ability to coordinate the metabolic flux through the C4 and C3 cycles, and that φ is relatively constant between species and across different growth conditions.…”
mentioning
confidence: 99%
“…In fact, using the full formulation of the Δ 13 Cleaf model developed byFarquhar (1984) typically indicates little to no change in φ under low light[17,36,37,41]. Additionally, φ was generally found to acclimate to rapid changes in light quality[42]. Therefore, direct measurements of Δ 13 Cleaf generally indicate that C4 plants have a remarkable ability to coordinate the metabolic flux through the C4 and C3 cycles, and that φ is relatively constant between species and across different growth conditions.…”
mentioning
confidence: 99%
“…These environmental factors affect plants' growth, morphology, physiology and biochemistry. Many research works have shown that light plays key role in changing the traits of plants (Lee et al, 2013;Ranade and García-Gil, 2013;Adam and Cavaleri, 2014;Kuehne et al, 2014;Lavinsky et al, 2014;Sun et al, 2014). Plants' morphological and physiological differences in growth reactions to shade or low light intensity are exceedingly important in all types of forests in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of PPDK, rbcL, ATPase beta subunit was up-regulated in the leaf proteome as heat-response proteins of M. sinensis (Sharmin et al, 2013 ). In contrast with the acclimation experiments to single controlled environment factor (Sun et al, 2012 , 2014 ; Sharmin et al, 2013 ), 80.8% of M. lutarioriparius photosynthetic transcripts were coordinated at transcription level across two contrasting field environments.…”
Section: Discussionmentioning
confidence: 79%
“…In studying the acclimation of M. × giganteus to transient changes in light quality, transient changes in light treatments quickly lower the rate of net CO 2 assimilation and disrupt the coordination of C 3 and C 4 cycles, which potentially seems to affect cyclic electron flux around photosystem I and chloroplast rearrangement (Sun et al, 2012 , 2014 ). Meanwhile, M. × giganteus acclimates poorly to low water availability (Clifton-Brown and Lewandowski, 2000 ) and photosynthetic performance is reduced by a decrease in stomatal conductance, which is followed with a decrease in chlorophyll content and chlorophyll fluorescence (Ings et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%